From SCAMP Singularity to Incognoscible - Portovedo, Henrique (2023)
Drawing on the development and technical possibilities of the Hybrid Augmented Saxophone of Gestural Symbioses (HASGS), this music proposal challenges the performance practice context in which the interpreter is required to be a creative agent within a multidimensional context of sonic manipulation, improvisation, expressive extension, augmentation and programming. HASGS emerges both as a means of contributing to optimising this new virtuosity and as a result of the changing role of the performer as creator by means of generating sonic material. This work goes from the performance of Singularity 1 to Incognoscible, a sound- installation based on the sonic material generated at Singularity 1. HASGS was developed a project aimed at enhancing performance by electronically controlling parameters in mixed music performed via the mechanical instrument, thus reducing recourse to external control devices for electronic purposes. After three preliminary prototypes, the current system is constituted by an ESP32 card, providing Bluetooth and Wifi connectivity, while based on a digital production solution able to be directly integrated into the instrument’s body, thus transforming the saxophone into a hybrid instrument – both an acoustic instrument and an electronic controller. Similar to any augmented instrument or electronic equivalent, HASGS introduces an arbitrary factor into performance as the acoustic properties of the instrument’s material and shape do not determine the sounds emitted, but it has the potential to control algorithmic systems in order to generate material in real time. Although instrumental music is by definition technologically mediated, digitalization has fundamentally changed music production, transmission, and reception, in ways perhaps not fully foreseeable at its origins. SCAMP Singularity is actually a serie of studies for saxophone, that were developed over SCAMP framework in Python created by Marc Evanstein, designated to act as a hub connecting the composer-programmer- performer to different resources for playback and notation. Here, starting with SCAMP Singularity 1, the piece for alto saxophone is a semi-improvisatory work in which the performer has to deal with two temporalities – determining the future sound environment and improving according to that choices. Namely, the performer's gesture changes, the texture of the electronic sounds, providing a sonic background to the saxophone's melodic discourse and rhythmic impulses. Therefore, the performer needs to simultaneously take into consideration two moments, namely, the present (i.e., the standards imposed by the software but created by the past action of the performer), and the future (i.e., the gestural connection with the sensors). SCAMP Singularity may therefore be defined as a multitemporal feedback loop. Incognoscible is a sound installation mediated by a software developed in Max/MSP, which performs algorithmic and generative functions. The composite electronic sound elements are distributed throughout the space using multiple possible configurations of the spatial systems. In this example, a quadrophonic configuration is used, in which the various sound sources are renewing their positioning and moving in space in an automated way and reacting to the position of the spectator, the same way light is reacting. As we are immersed in computation, living in a post-humanistic and post-digital world, in which it becomes fundamental to artistic practice, to artworks, and the aesthetic experience, the integration of digital technology and mechanical instruments would not only deconstruct this distinction between electronic and instrumental music, enormously amplify the scope of extended and augmented techniques, but would also question, the traditional understanding of composer, performer and programmer, and their interrelationships. Technology is moving faster than musical practices and we are taking some snapshots of techniques applied in musical composition and performance, techniques whose materialities will be quickly replaced with new ones, but whose embodied structures continue and become re-implemented in later technical objects as a recycling of skills. Understanding how emerging digital musical technologies trace their concepts, design and functionality to practices in the current cultural epoch will bring to light a study of new- media archeology, conceptual epistles and performative paradigms, directed, in other words, to the study of how the new technologies of mixed music-making trace their design to the practices of material, symbolic, signal inscription, listening experiences and how practice is transforming and leading to creation.